(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. The purposes of this study were to determine the quantitative characteristics of the articles published in sports and exercise psychology journals in four quartiles of Web of Science and to understand whether these characteristics had any effect on citation. Methods. Sport and exercise psychology journals indexed under the Sport Sciences subject category were included in the study. A total of 172 articles published in 2017, which was the most recent date meeting inclusion criteria, were collected from four sport and exercise psychology journals included: Psychology of Sport and Exercise (Q1), Journal of Sport and Exercise Psychology (Q2), Sport Psychologist (Q3), and International Journal of Sport Psychology (Q4). Results. The articles published in Q1 journal were multi-institutional and multinational. Besides, they had longer abstracts and discussions and cited more references. The results revealed that multinational articles and articles with structured abstracts had higher citations than single country articles and articles with unstructured abstracts. The number of affiliated countries and references, and longer titles, abstracts, and introductions were found significantly associated with the number of citations. The bibliometric analysis indicated that the UK, the USA, and Canada were the major contributing countries. Conclusion. This study is the first attempt to investigate the characteristics of articles published in different WoS quartiles within the field of sports and exercise psychology. The findings of the study may help researchers to improve their citation count. Keywords: scientific productivity, essential science indicators, journal impact factor, Web of Science, scientometrics.